Detection of Mutations in Precore and Basal Core Region in HBeAg Negative Chronic Hepatitis B Patients from Jaipur - Madhavi Vyas , Pratibha Sharma , Himanshu Sharma , Farah Deeba , Bharti Malhotra (RUHS Journal of Health Sciences, 2023)
Introduction: Chronic hepatitis B (CHB) has been considered a global health problem for years. Different mutations in the precore and basal core promoter (PC/BCP) region result in HBeAg negative hepatitis. G1896A, which is the most frequently observed mutation in the PC region, acts by insertion of a premature stop codon in the concerned ORF while the A1762T/G1764A double mutation in the BCP region acts by termination of HBeAg expression. Various mutants and genotypes are significantly associated with diagnostic failure, response to antiviral therapy, liver fibrosis, cirrhosis and hepatocellular carcinoma (HCC). Therefore, determination of these mutations and their correlation with clinical manifestations is of utmost importance specially in HBeAg negative CHB patients. Methodology: 10 HBsAg positive, HBcIgM, and HBeAg 3 negative CHB patients with viral load >10 IU/mL attending SMS hospital, Jaipur during year 2021 were tested for nested PCR and sanger sequencing was done for 261 bp fragment of PC/BCP region. Multiple sequence alignment and mutation analysis was done using MEGA software. Results: Genotype D was detected in 9/10 (90%) samples and genotype A in 1/10 (10%) samples. Mutations were detected in 5/10 samples (50%) and all belonged to genotype D. Out of these 5 isolates, 3 (30%) showed the classical PC mutation G1896A, whereas in the BCP region double mutation (A1762T/G1764A) was detected in 2 (20%) cases. Conclusion: HBV genotypes and PC/BCP mutations are useful for predicting disease prognosis and help clinicians in planning individualized treatment regimens for HBeAg negative CHB patients.